When Theatre Becomes a Refuge: The empowering journey of Al-Harah Theatre for Palestinian children - Barham, Marina; Matar, George (Education & Theatre, 2025)
Amid the complex political, social and economic challenges that Palestinians endure daily, there is an increasing and urgent need for creative tools that provide children with a safe space in which to express themselves freely. In a context where genocide has caused the deaths of over 80,000 people, particularly children, and injuries to over 180,000 more, trauma and fear often stifle childhood innocence. The arts become a powerful form of resistance, resilience, healing and hope. This article explores the pioneering work of Al-Harah Theatre, an organisation that has integrated drama and theatre into the fabric of Palestinian schools, treating them not merely as extracurricular artistic pursuits, but as vital instruments of psychological, educational and cultural empowerment. Drawing on over 20 years’ experience of working in schools, refugee camps and community centres, this comprehensive account illustrates how theatre can be a catalyst for emotional healing, self-expression and hope in the lives of Palestinian children. Theatre and the arts have also played a crucial role in supporting women and people with disabilities across both the West Bank and the Gaza Strip. These creative practices have become vital in helping entire communities to confront, process and heal from the ongoing trauma and devastation caused by the israeli occupation.